Attachment theory and culture: parenting in Latin America and rural Peru from an attachment theory perspective - Fourment Sifuentes, Katherine Gretel (2022)
Descargue el texto completo en el repositorio institucional de la Universiteit Leiden: https://hdl.handle.net/1887/3303342